Effect Of PROM and Hand Grip Ball Exercise in Stroke Patient With Left Hemiparesis : A Case Report - Ridha Ghina Nurjanah; Popon Haryeti (Jurnal Ners, 2025)
Hemiparesis is a common complication after stroke that causes decreased muscle strength and mobility. This condition becomes more complex when accompanied by comorbid diseases such as Systemic Lupus Erythematosus (SLE), thus requiring a more integrated rehabilitation approach. This study aims to provide the effect of a combination of Passive Range of Motion (PROM) training and finger grip ball training on increasing muscle strength in infarction stroke patients with left hemiparesis and SLE comorbidity. The intervention was carried out in the stroke unit for four consecutive days, twice a day, with a duration of 20 minutes of PROM and 7–10 minutes of finger grip ball training each session. Muscle strength assessment was carried out using the Manual Muscle Testing (MMT) Scale before and after the intervention. The results showed that before therapy, the strength of the left extremity muscles was at a minimal contraction level (score 1/5), and increased to being able to perform active movements against moderate resistance (score 4/5) after the intervention. During therapy, no side effects were found, and the patient was able to tolerate the exercise well. These findings support that the combination of PROM and finger grip ball exercises can be an effective and safe non-pharmacological rehabilitation strategy to improve muscle strength in Ny. R stroke patients with hemiparesis and SLE comorbidity. Hemiparesis merupakan komplikasi umum pasca-stroke yang menyebabkan penurunan kekuatan dan mobilitas otot. Kondisi ini menjadi lebih kompleks apabila disertai penyakit komorbid seperti Lupus Eritematosus Sistemik, sehingga memerlukan pendekatan rehabilitasi yang lebih terintegrasi. Studi ini bertujuan untuk mengevaluasi pengaruh kombinasi latihan Passive Range of Motion (PROM) dan latihan bola genggam jari terhadap peningkatan kekuatan otot pada pasien stroke infark dengan hemiparesis sinistra dan komorbid LES. Intervensi dilakukan di unit stroke selama empat hari berturut-turut, dua kali sehari, dengan durasi 20 menit PROM dan 7–10 menit latihan bola genggam jari setiap sesi. Penilaian kekuatan otot dilakukan menggunakan skala Manual Muscle Testing (MMT) sebelum dan sesudah intervensi. Hasil menunjukkan bahwa sebelum terapi, kekuatan otot ekstremitas kiri berada pada tingkat kontraksi minimal (skor 1/5), dan meningkat menjadi mampu melakukan gerakan aktif melawan resistensi sedang (skor 4/5) setelah intervensi. Selama terapi, tidak ditemukan efek samping, dan pasien mampu mentoleransi latihan dengan baik. Temuan ini mendukung bahwa kombinasi PROM dan latihan bola genggam jari menjadi strategi rehabilitasi nonfarmakologis yang efektif dan aman untuk meningkatkan kekuatan otot pada Ny.R pasien stroke dengan hemiparesis dan LES.